2018
DOI: 10.4103/ortho.ijortho_563_17
|View full text |Cite
|
Sign up to set email alerts
|

Management of Talar Body Fractures

Abstract: Fractures of talar body are uncommon injuries often associated with fractures of other long bones and in polytraumatized patients. The integrity of the talus is essential for the normal function of the ankle, subtalar, and midtarsal joints. The relative infrequency of this injury limits the number of studies available to guide treatment. They occur as a result of high-velocity trauma and are therefore associated with considerable soft tissue damage. Axial compression with supination or pronation is the common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…It is well known that the different fixation directions and fixation methods of screws are not only the main factors affecting the stress distribution of talus, but also the key factors to promote fracture healing. Several reports have shown that proper internal fixation can provide a good mechanical environment for talus neck fracture and improve the cure rate of talus neck fracture [23,24]. After the fracture of the talus neck was incised and fixed, the stress on the fracture surface is too large, which will lead to an increase in the probability of secondary fracture and even bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the different fixation directions and fixation methods of screws are not only the main factors affecting the stress distribution of talus, but also the key factors to promote fracture healing. Several reports have shown that proper internal fixation can provide a good mechanical environment for talus neck fracture and improve the cure rate of talus neck fracture [23,24]. After the fracture of the talus neck was incised and fixed, the stress on the fracture surface is too large, which will lead to an increase in the probability of secondary fracture and even bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that functional outcomes of those cases with peroneal tendon dislocation were not uniformly recorded, which precludes comparison to those with talus fractures with no concurrent peroneal tendon dislocation. However, morbidity associated with isolated peroneal tendon dislocation has been described in literature and touched upon earlier in this discussion [17][18][19].…”
Section: Discussionmentioning
confidence: 95%
“…Chronic dislocation is associated with tear of the peroneus brevis due to attrition against the posterolateral ridge of the fibula. This adds to the morbidity of talus fractures and may lead to inferior outcomes of surgical treatment (17)(18)(19). Another implication of the presence of peroneal tendon dislocation is that it may affect approach selection for open reduction and internal fixation to allow for examination and treatment of the peroneal dislocation while maintaining maximum exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture of the talar head is relatively rare, with a described incidence of <10% of talar fractures. is pattern is caused by a combined dorsiflexion and inversion force that longitudinally loads the talus, resulting in a shear fracture across the talar head [16]. As a result, the medial column is functionally shortened, often resulting in a cavovarus foot with abnormal loading of the lateral column.…”
Section: Talar Fracturementioning
confidence: 99%
“…Treatment of talar head fractures varies from conservative immobilization to percutaneous pinning and to open reduction and internal fixation of displaced fragments [16]. In cases of late or missed diagnosis, salvage arthrodesis may be an additional option.…”
Section: Talar Fracturementioning
confidence: 99%